How did the elimination of the earnings test above the normal retirement age affect retirement expectations? - Pierre-Carl Michaud; Arthur van Soest (Institute for the Study of Labor (IZA), 2007)
We look at the effect of the 2000 repeal of the earnings test above the normal retirement age (NRA) on retirement expectations of male workers in the Health and Retirement Study (HRS). Using administrative records on Social Security benefit entitlements linked to the HRS survey data, we can distinguish groups of respondents according to how, before the repeal, the earnings test would have affected their marginal wage rate after the NRA. We use panel data models with fixed and random effects to investigate the effect of the repeal on the subjective probability to work full-time after the NRA as well as after age 62. We find that male workers whose marginal wage rate increased because the earnings test was repealed, had the largest increase in this probability. We find no significant effects of the repeal on the probability to work full-time past age 62. Since the tax introduced by the earnings test was small when accounting for actuarial benefit adjustments, our results suggest that male workers misperceive the complicated rules of the earnings test.
Keywords: 330; Altersgrenze; Erwartungstheorie; Gesetzliche Rentenversicherung; Ältere Arbeitskräfte; Arbeitsangebot; USA